2002
DOI: 10.1037/0012-1649.38.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Maternal adjustment and infant outcome in medically defined high-risk pregnancy.

Abstract: Biological and psychosocial risk factors in high-risk pregnancy and their relation to infant developmental outcomes were explored in a sample of 153 pregnant Israeli women who had pregestational diabetes mellitus, gestational diabetes mellitus, or were nondiabetic. Questionnaires on coping and resources as well as well-being and distress during the 2nd trimester were administered. Estimates of maternal fuels (HbAlc and fructosamine) were obtained throughout pregnancy. At 1 year, offspring were administered the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 43 publications
0
61
0
2
Order By: Relevance
“…The majority of studies were conducted in Sweden [22,25-27,34] and the USA [31,33,35-38], and the remaining studies were conducted in Australia [28], Greece [30], Israel [32], Italy [29], and the UK [19,23]. The focus of nine studies was the pregnancy itself [25,26,30-33,35,36,38], while three focused on the immediate post-partum phase [25,26,37] and six focused on the postnatal phase [22,27-29,34,37] as illustrated in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of studies were conducted in Sweden [22,25-27,34] and the USA [31,33,35-38], and the remaining studies were conducted in Australia [28], Greece [30], Israel [32], Italy [29], and the UK [19,23]. The focus of nine studies was the pregnancy itself [25,26,30-33,35,36,38], while three focused on the immediate post-partum phase [25,26,37] and six focused on the postnatal phase [22,27-29,34,37] as illustrated in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies [29-32,37,38] included women with gestational diabetes as well as those with T1DM but our current review focused only on data relating to women with T1DM. Samples of women with T1DM ranged N = 7-23 in the qualitative studies and N = 30-105 in the quantitative studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Coping strategies are considered relevant for infant developmental outcomes (Levy-Shiff et al 1998;Levy-Shiff et al 2002) and postpartum depression (Terry et al 1996;Honey et al 2003a;de Tychey et al 2005). Mikulincer and Florian found that avoidant women showed weak attachments to their fetuses and showed negative mental health in the first and third trimesters of their pregnancies (Mikulincer and Florian 1999).…”
Section: Introductionmentioning
confidence: 99%